Partnership, information and socio-cultural dynamization in small Brazilian municipalities: concrete examples - Barros, María Elena (2005)
The text came from the UNESP-Project in Partnership with the Public Administration: City of Echaporã ‖, a multidisciplinary project, interdepartmental and that results from a term partnership signed between the State University / Campus Marilia, the Regional Office of Articulation Planning and the Municipality of Echaporã. Given the serious social problems diagnosed in this county Administrative Region of Marilia, somaramse forces and, since April 2002, Echaporã account with the performance of a design matrix that involves the community in six (6) subprojects, among which a which emphasizes the dissemination of information (the public library as a center of information and knowledge irradiator for urban and rural areas, seeking to enter the Society daInformação). By their nature, the project-matrix is considered open and can accommodate new subprojects, where they concern the problems identified in the initial diagnosis. For its validity, each subproject has its own methodology, some innovative and will be subject to further systematization and dissemination, however, after a few months of deployment, the results show the correctness of community involvement (being representative) in all discussions and steps of research, and activities developed, widely disseminated to the target audience.   The membership of the community, the leaders and the authorities can be considered a good barometer of the actions carried out in Echaporã and evidence of change in information culture that is already noticeable in the city, setting the socio-cultural dynamics of the same, in terms a new public policy to be strengthened with the participation of specialists in this specific area, in direct work with local managers, in this case, specific examples relating to the strength of information in the process of change in small municipalities.